Pemikiran Al-Fudholi dalam Kitab Kifayatul Awam Tentang Sifat Allah - Akbar, Sabila; Nafis, Addurun; Sukiman, Sukiman; Suryani, Ira (Islam & Contemporary Issues, 2023)
The book "Kifayatul Awam" by Al-Fudholi is one of the important works of Islamic literature in the context of religious and legal thought. This book has become a primary reference material in Islamic law in various societies. This article aims to analyze twenty characteristics of Al-Fudholi's thought found in the book "Kifayatul Awam." This research employs a text analysis method to identify and explain the characteristics of Al-Fudholi's thought in his book. The results of the analysis indicate that these twenty characteristics of thought encompass various aspects of Islamic law, ethics, and beliefs. Some of these characteristics include concepts related to justice, worship, transactions, and social responsibility. This study provides a deeper understanding of Al-Fudholi's thought in the context of Islamic religion and law. It can also serve as an important reference for those studying and examining classical Islamic literary works, contributing to a better understanding of Islamic teachings in general.